2003
DOI: 10.1021/jm030347n
|View full text |Cite
|
Sign up to set email alerts
|

Diflunisal Analogues Stabilize the Native State of Transthyretin. Potent Inhibition of Amyloidogenesis

Abstract: Analogues of diflunisal, an FDA-approved nonsteroidal antiinflammatory drug (NSAID), were synthesized and evaluated as inhibitors of transthyretin (TTR) aggregation, including amyloid fibril formation. High inhibitory activity was observed for 26 of the compounds. Of those, eight exhibited excellent binding selectivity for TTR in human plasma (binding stoichiometry >0.50, with a theoretical maximum of 2.0 inhibitors bound per TTR tetramer). Biophysical studies reveal that these eight inhibitors dramatically sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
266
0
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(283 citation statements)
references
References 80 publications
(233 reference statements)
11
266
0
5
Order By: Relevance
“…TTR aggregation has been a model system for this approach, because small molecules, including the nonsteroidal anti-inflammatory drug diflunisal and many of its derivatives, are reported to stabilize the native tetrameric structure (31,32,46). In this study, we directly investigated the effect of diflunisal on F-rTTR tetramer structure by analysis of the s isotherms in the presence and absence of drug.…”
Section: Discussionmentioning
confidence: 99%
“…TTR aggregation has been a model system for this approach, because small molecules, including the nonsteroidal anti-inflammatory drug diflunisal and many of its derivatives, are reported to stabilize the native tetrameric structure (31,32,46). In this study, we directly investigated the effect of diflunisal on F-rTTR tetramer structure by analysis of the s isotherms in the presence and absence of drug.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, Ͻ1% of TTR in the plasma and cerebrospinal fluid is bound to thyroxine, allowing us to target these sites with other small aromatic molecules to prevent amyloidogenesis (36). By using both focused screening and structure-based design, our laboratory has previously reported several classes of compounds that are capable of inhibiting TTR fibril formation by binding to the thyroxine sites (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Good inhibitors bind with high affinity, dissociate slowly, and exhibit high binding selectivity to TTR in the blood.…”
mentioning
confidence: 99%
“…In addition, it is imperative to notice that DES binding mediates several new intersubunit hydrophilic and hydrophobic interactions that will decrease the capacity of the protein to dissociate upon DES binding. In fact, compounds that bind tightly in the TTR binding channel should increase the energetic barrier associated with protein dissociation, and a number of small molecules representative of very distinct structural families are emerging as inhibitors of TTR amyloid formation (13,14,45,46). Furthermore, reported data indicate that the cytotoxic species are oligomers, which occur prior to fibril formation (47).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that binding of the natural ligand T 4 to the TTR central hydrophobic channel stabilizes the tetramer and consequently reduces amyloid fibril formation (12). In the past few years, considerable effort has been directed to the discovery of small molecules that could prevent TTR dissociation by binding in the protein central channel (13,14). Actually, stabilization of the native tetrameric fold, upon high affinity binding of a small compound, is considered to be a potential therapeutic strategy to senile systemic amyloidosis and familial amyloidotic polyneuropathy variants (15,16).…”
mentioning
confidence: 99%